The limitations of neoliberal logic in the anti-corruption industry: lessons from Papua New Guinea - Walton, Grant W. (Crime, law and social change, 2013)
To acknowledge concerns about the rising power of the private sector, key international anti-corruption organisations have supported initiatives that emphasise the role that businesses play in corruption. Yet the way these initiatives have impacted the practices and perceptions of anti-corruption organisations in developing countries has received scant attention. As businesses can be key perpetrators of corruption, understanding the way anti-corruption organisations respond to the private sector can highlight the efficacy of anti-corruption efforts. Drawing on interviews with anti-corruption policy makers in Papua New Guinea (PNG) conducted between 2008 and 2009, this article shows how two international anti-corruption organisations perceived and worked with the private sector. It finds that there have been some initiatives designed to address, and raise awareness about private sector corruption in the country, reflecting international trends. At the same time the private sector is viewed, often uncritically, as an anti-corruption champion; this has affected the way anti-corruption organisations engage with businesses operating in the country. This article argues that despite a change in international discourse about the private sector’s role in corruption, in developing countries like PNG, neoliberal logic about the nature of the state still guide anti-corruption activity. These findings have implications for the efficacy of international anti-corruption efforts.